Standard for Emergency, Continuity, and Crisis Management: Preparedness, Response, and Recovery (The National Fire Protection Association., 2024)
NFPA® 1660, Standard for Emergency, Continuity, and Crisis Management: Preparedness, Response, and Recovery, establishes a common set of requirements for emergency management and business continuity programs; mass evacuation, sheltering, and re-entry programs; and the development of pre-incident plans for emergency response personnel. As part of the NFPA Emergency Response and Responder Safety Document Consolidation Plan, this first-time 2024 edition combines the widely referenced NFPA 1600®, Standard on Continuity, Emergency, and Crisis Management; and NFPA 1616, Standard on Mass Evacuation, Sheltering, and Re-entry Programs; and NFPA 1620, Standard for Pre-Incident Planning, to increase usability, reduce errors and conflicts, and ultimately produce a higher quality document. From first responders and safety officials to facility owners and crisis managers, the standard helps ensure you have an effective pre-incident plan and everyone knows how to respond in coordination to a broad range of emergency scenarios. Changes to incorporated criteria in NFPA 1660 include: New single-set of terminology in Chapter 3 to ensure consistency and continuity throughout the entire document Updated reference chapters to increase usability General revisions to bring consolidated content into alignment and create a more cohesive single standard.
NFPA 1660 to nowa, skonsolidowana norma, która służy jako jedno, kompleksowe źródło informacji do planowania zarządzania kryzysowego na wszystkich poziomach. Spełnia ona potrzeby zarówno poszczególnych firm, jak i całych społeczności, łącząc i zastępując normy NFPA 1600; NFPA 1616, Standard dotyczący programów masowej ewakuacji, schronienia i powrotu do środowiska; oraz NFPA 1620, Standard dotyczący planowania przed zdarzeniem
Keywords: Zarządzanie kryzysowe; sytuacje nadzwyczajne; Ewakuacja ludności